Soft-winged flower beetles (Coleoptera: Malachiidae) of the United Arab Emirates - Tshernyshev, Sergei E. (European Journal of Taxonomy, 2022)
Soft-winged flower beetles from the United Arab Emirates are studied for the first time. Three new genera, Tonyattalus gen. nov. of the tribe Attalini, Tonycolotes gen. nov. of the tribe Colotini, and Arabotroglops gen. nov. of the tribe Troglopini, and two species, Tonyattalus vanharteni gen. et sp. nov. and Arabotroglops longantennatus gen. et sp. nov., are described. Tonycolotes kovari (Švihla, 1987) gen. et. comb. nov. is recorded from the United Arab Emirates for the first time and transferred from the genus Colotes Erichson, 1840. All species discussed in the paper are described and illustrated. The fauna of soft-winged flower beetles of the Arabian Peninsula is reviewed.